Long term impact of poor birth condition on social and economic outcomes in early adulthood. (7th June 2011) - Odd, D E; Gunnell, D; Lewis, G; Rasmussen, F
Abstract : Objective: To investigate the association of poor birth condition with long term social and economic outcomes at age 25 to 31 years. Design: Population-based cohort study using data derived from linkage of routinely collected Swedish data. Setting and participants: All term infants born in Sweden between 1973 and 1979 identified from the Swedish birth registry (n=651 615). Infants were categorized into three groups: (1) infants with normal (>7) Apgar score at 1 or 5 min of age without encephalopathy, (2) infants with a low (<7) Apgar score at 1 and 5 min of age without encephalopathy and (3) infants with a low (<7) Apgar score at 1 and 5 min with evidence of encephalopathy. Main outcome measures: Achievement of a university education and participant's income in early adulthood. Results: Infants with low Apgar scores who did not develop encephalopathy were less likely to have attended university (OR 1.14 (1.05 to 1.23)) and were more likely to have no income from work (OR 1.19 (1.07 to 1.32)) than those born in good condition. Infants who developed encephalopathy also had greater risks of these adverse outcomes (not attended university, OR 1.94 (1.13 to 3.33)); no income from work, OR 3.08 (1.89 to 5.01)). Conclusions: Infants born in poor condition had worse measures of social performance than their peers and this association was not restricted to those infants who developed obvious neurological symptoms in the neonatal period. However, even in infants with likely encephalopathy over a half obtained employment and a third attended university.